2001
DOI: 10.1074/jbc.m101895200
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the Rat GRIK5 Kainate Receptor Subunit Gene Promoter and Its Intragenic Regions Involved in Neural Cell Specificity

Abstract: The GRIK5 (glutamate receptor ionotropic kainate-5) gene encodes the kainate-preferring glutamate receptor subunit KA2. The GRIK5 promoter is TATA-less and GCrich, with multiple consensus initiator sequences. Transgenic mouse lines carrying 4 kilobases of the GRIK5 5-flanking sequence showed lacZ reporter expression predominantly in the nervous system. Reporter assays in central glial (CG-4) and non-neural cells indicated that a 1200-base pair (bp) 5-flanking region could sustain neural cell-specific promoter … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
12
0

Year Published

2002
2002
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 63 publications
1
12
0
Order By: Relevance
“…Independent studies have shown that Sp1 has functional implication in expression of some of NRSF target genes including N -methyl- d -aspartate receptors, dynamin I, synaptophysin and glutamate receptor ionotropic kainate-5 genes (2224). For MOR gene regulation, Sp1 factor acts as a major positive regulator by binding two cis -elements (distal and proximal promoters) located at −340 through −300 residues from the translation start site while Sp3 has a minor effect by binding to one of these elements (25).…”
Section: Resultsmentioning
confidence: 99%
“…Independent studies have shown that Sp1 has functional implication in expression of some of NRSF target genes including N -methyl- d -aspartate receptors, dynamin I, synaptophysin and glutamate receptor ionotropic kainate-5 genes (2224). For MOR gene regulation, Sp1 factor acts as a major positive regulator by binding two cis -elements (distal and proximal promoters) located at −340 through −300 residues from the translation start site while Sp3 has a minor effect by binding to one of these elements (25).…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, a 77-bp sequence termed the kainate cell-specific enhancer region, involved in cell-specific expression, includes a functional Sp1 site that when placed downstream of the Grik5 promoter, silenced reporter expression in NIH3T3 fibroblasts and attenuated activity in CG-4 cells. These studies show that elements contributing to tissue-specific expression are contained within the first exon (Chew et al, 2001).…”
Section: B Kainate Receptors Grik1 To Grik5mentioning
confidence: 99%
“…Transgenic mouse lines carrying 4 kb of the 5Ј-flanking sequence showed lacZ reporter expression predominantly in the nervous system. Reporter assays in central glial (CG-4) and non-neural cells indicated that a 1200-bp 5Ј-flanking region could sustain neural cell-specific promoter activity (Chew et al, 2001). Sp1 binding suggests a functional role for Sp1 in initiatormediated activation of Grik5 transcription that involves transcription factor II D-mediated basal activity (Chew et al, 2001).…”
Section: B Kainate Receptors Grik1 To Grik5mentioning
confidence: 99%
See 1 more Smart Citation
“…Gel Shift Assay-Mouse brain nuclear extract was prepared as described previously with modifications (42). Briefly, the brain tissue was frozen in liquid nitrogen and shattered into tissue powder.…”
mentioning
confidence: 99%